Frequency tracking and mitigation method based on CPHD filter and adaptive multiple linear Kalman notch filter for multiple GNSS interference. Issue 4 (14th January 2020) - Kim, Sun Young; Kang, Chang Ho; Park, Chan Gook
Abstract: In this paper, a frequency tracking method based on a cardinalized probability hypothesis density (CPHD) filter with cardinality compensation and fuzzy‐c means (FCM) clustering is proposed to precisely estimate multiple interference frequencies in the received Global Navigation Satellite System (GNSS) signal. In addition, an adaptive multiple linear Kalman notch filter is applied in order to mitigate multiple GNSS interference signals by using tracking results from the proposed CPHD filter. The cardinality refers to the number of interference frequencies, and estimation accuracy on the cardinality has an effect on the tracking and mitigation performance of the filter. For that reason, the cardinality compensation process and FCM clustering are added in the CPHD filter. The proposed tracking and mitigation method is evaluated by theoretical analysis including simulations. It is confirmed that the proposed algorithm has better tracking and mitigation performance compared with the conventional algorithms.